Challenges to religious liberty in the twenty-first century - Bradley, Gerard V., 1954- (New York : Cambridge University Press, 2012)
"Almost everyone today affirms the importance and merit of religious liberty. But religious liberty is being challenged by new questions (for example, use of the niqab or church adoption services for same-sex couples) and new forces (such as globalization and Islamism). Combined, these make the meaning of religious liberty in the twenty-first century uncertain. This collection of essays by ten of the world's leading scholars on religious liberty takes aim at these issues. The book is arranged around five specific challenges to religious liberty today: the state's responsibility to prevent coercion and intimidation of believers by others within the same faith community; the U.S.'s basic moral responsibilities to promote religious liberty abroad; how to understand and apply the traditional right of conscientious objection in today's circumstances; the distinctive problems presented by globalization; and the viability today of an 'originalist' interpretation of the First Amendment religion clauses"--Provided by publisher.
Part I. "Originalist" Jurisprudence of the Religion Clauses in the Twenty-First Century: 1. The establishment clause and the 'problem of the church' / Steven D. Smith; 2. Dueling Clios: Stevens and Scalia on the original meaning of the establishment clause / Gerard V. Bradley -- Part II. Coercion of Manipulation of Religious Beliefs and Practices: States' Basic Responsibilities: 3. Coercian and religious exercises / Kent Greenawalt; 4. Religious freedom and (and in) institutions / Richard W. Garnett -- Part III. Understanding the Traditional Right of "Conscientious Objection": the New Century's Greatest Challenges: 5. Free exercise, religious conscience, and the common good / Christopher Wolfe; 6. Conscience, religion, and the state / Christopher Tollefsen -- Part IV. The Unique and Unprecedented Challenges of Globalization to Religious Liberty: 7. Globalization and the free exercise of religion worldwide / Jose; Casanova; 8. The irony of a globalizing future: economics, technology, identity, and religious liberty / William Inboden -- Part V. The United States' Basic Moral Responsibilities to Promote Religious Liberty Abroad: 9. A foreign policy of religious freedom: theoretical and evidentiary foundation / Daniel Philpott; 10. International religious freedom and moral responsibility / Thomas Farr.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Freedom of religion; POLITICAL SCIENCE / Government / General; RELIGION / Religion, Politics & State; Electronic books